Dyder i danske historielærebøger siden oplysningstiden:ingen - Haue, Harry (Yesterday and Today, 2018)
Artiklen indeholder en analyse af danske historielærebøger over tre århundreder med fokus på deres indhold af dydsorienteret fremstilling. Beaten down, sickly, virtue has now been allowed to enter in all its tatters and sit in the corner, as long as it doesn’t raise its voice (A Solzhenitsyn, The Gulag Archipelago. London, Collins/Fontana, 1974, p. 175) The above quoted statement by the famous Russian author, Alexander Solzhenitsyn, can to my opinion be interpreted as a dream of devitalization of good, old Russian virtues, which the communist regime had silenced and placed in the corner. Then I reflected on the status of virtues in my own country, and especially what history education had done to stick to virtues, which I have encountered in my earlier research as dominant in the 18th century educational discourse? My provisional examinations are presented in this article, where I focus on the impact of virtues in a sample of more popular Danish history textbooks over three centuries. Research in textbooks is closely connected to the societal context and a brief summary of the development in Denmark since the Enlightenment is appropriate, especially for the foreign reader, in order to understand the textbooks in a proper context. In the 18th century the Danish king was the absolute ruler of Denmark, Norway and the North Atlantic islands. Moreover he was the sovereign in the deuces Schleswig and Holstein and of course in the colonies in India, Africa and Caribbean. This multicultural state was transformed in the 19th century; in 1814 Norway was ceded to Sweden, and in 1864 Schleswig and Holstein were after a bloody war, taken over by Prussia. Hence Denmark was one of the smaller countries in Europe, however now a national state. In 1814 compulsory seven-year school attendance was implemented for all girls and boys, and in the second half of the century agriculture and industry underwent a remarkable growth. In 1849 the absolute ruling king signed a constitution, which introduced partial democratic elections. ...